2015
DOI: 10.1155/2015/594656
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Aromatase by Phytoestrogens

Abstract: The aromatase enzyme catalyzes the conversion of androgens to estrogens in many human tissues. Estrogens are known to stimulate cellular proliferation associated with certain cancers and protect against adverse symptoms during the peri- and postmenopausal intervals. Phytoestrogens are a group of plant derived naturally occurring compounds that have chemical structures similar to estrogen. Since phytoestrogens are known to be constituents of animal/human food sources, these compounds have received increased res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 101 publications
3
43
0
3
Order By: Relevance
“…Bioactive effects have been reported among them, such as antioxidant, anti-inflammatory, anticancer and anti-aromatase (Olthof et al, 2001;Gülçin, 2006;Kim et al, 2011;Marrassini et al, 2011;Choo et al, 2012;Lu et al, 2012;Lee et al, 2013;Shu-Yao et al, 2013). However, in vivo effects (especially anticancer and anti-aromatase), of both flavonoid rich extracts and purified extracts are still debated (Saarinen et al, 2001;Moon et al, 2006;Genoux et al, 2011;Lephart, 2015). The works by Dhawan & Sharma (2002, 2003; Dhawan (2003) and review by Dhawan et al (2004), suggest that the compound known as BZF, which is described as a trisubstituted α-naphthoflavone isolated from the methanolic extract of P. incarnata, has a strong antiaromatase activity by restoring libido decline, sperm count and fertility in male rats exposed to substances such as cannabinoids, alcohol or nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive effects have been reported among them, such as antioxidant, anti-inflammatory, anticancer and anti-aromatase (Olthof et al, 2001;Gülçin, 2006;Kim et al, 2011;Marrassini et al, 2011;Choo et al, 2012;Lu et al, 2012;Lee et al, 2013;Shu-Yao et al, 2013). However, in vivo effects (especially anticancer and anti-aromatase), of both flavonoid rich extracts and purified extracts are still debated (Saarinen et al, 2001;Moon et al, 2006;Genoux et al, 2011;Lephart, 2015). The works by Dhawan & Sharma (2002, 2003; Dhawan (2003) and review by Dhawan et al (2004), suggest that the compound known as BZF, which is described as a trisubstituted α-naphthoflavone isolated from the methanolic extract of P. incarnata, has a strong antiaromatase activity by restoring libido decline, sperm count and fertility in male rats exposed to substances such as cannabinoids, alcohol or nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…The protein result of aromatase gene has so far been found the same despite of the tissuespecific expression patterns of aromatase. The control aromatase gene expression at all levels: mRNA, protein, functional, and enzymatic activity has been considered as important not only for the treatment of breast cancer but also the critical role of aromatase enzyme [9], but as well in males, for example, in the cases of prostate cancers or gynecomastia [10]. In every pituitary tissue, there was an expression of aromatase enzyme inclusive autopsy samples and were most increased in patients with acromegaly than in another adenoma groups.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, phytoestrogens are a group of plant-derived compounds whose chemical structure is similar to animal and human estrogens [2][3][4][5][6][7][8][9][10]. They include a wide variety of secondary metabolites, i.e., hydroxybenzoic acid, hydroxycinnamic acids, anthocyanins, proanthocyanidins, flavonols, flavones, flavonones, isoflavones, stilbenes, and lignins, which are involved in protecting plants against ultraviolet radiation, aggression by pathogens, or stressrelated responses.…”
Section: Introductionmentioning
confidence: 99%
“…They include a wide variety of secondary metabolites, i.e., hydroxybenzoic acid, hydroxycinnamic acids, anthocyanins, proanthocyanidins, flavonols, flavones, flavonones, isoflavones, stilbenes, and lignins, which are involved in protecting plants against ultraviolet radiation, aggression by pathogens, or stressrelated responses. It has been reported that some terpenoids and saponins possess similar phytoestrogen effects [3][4][5]7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Several hundreds of these molecules are that improve poor milk secretion, e.g., cooked lettuce, watercress and wild fennel, boiled nettle tops, pasta with endive, and sesame in bread [58].…”
Section: Introductionmentioning
confidence: 99%